2018
DOI: 10.3343/alm.2018.38.5.413
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Function Analyzer-200 P2Y Results Are Predictive of the Risk of Major Adverse Cardiac Events in Korean Patients Receiving Clopidogrel Therapy Following Acute Coronary Syndrome

Abstract: BackgroundClopidogrel is one of the most commonly used anti-platelet agents in cardiovascular diseases. We analyzed the relationship between the platelet function analyzer (PFA)-200 P2Y (INNOVANCE PFA-200 System, Siemens Healthcare, Germany) results and occurrence of major adverse cardiac events (MACEs) in Korean patients with recent-onset acute coronary syndrome (ACS) taking clopidogrel.MethodsBetween August 2013 and June 2016, we prospectively enrolled 106 patients with recent-onset ACS who had been treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…Our study determined platelet function using the INNOVANCE PFA-200 system (Siemens Healthcare, Germany) which assesses P2Y12-receptor blockades in patients undergoing therapy with P2Y12-receptor antagonists [ 47 ]. Despite some reports indicating a positive correlation between the CT value, HTPR, and MACE frequency [ 13 , 20 , 48 , 49 ], our findings failed to associate the molecular genotype and phenotype of HPR. This result can be attributed to several factors; (a) low frequency of LOF alleles (b) absence of patients with the homozygous genotype for LOF alleles (c) high frequency CYP2C19 *1/*1 with CT suggestive of HPR (d) potential overestimation of patients HPR (technical limitation of PFA-200); (e) involvement of new intronic and/or promoter variants and (f) heterogeneity of response to clopidogrel due to genes not evaluated in this study [ 5 , 50 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study determined platelet function using the INNOVANCE PFA-200 system (Siemens Healthcare, Germany) which assesses P2Y12-receptor blockades in patients undergoing therapy with P2Y12-receptor antagonists [ 47 ]. Despite some reports indicating a positive correlation between the CT value, HTPR, and MACE frequency [ 13 , 20 , 48 , 49 ], our findings failed to associate the molecular genotype and phenotype of HPR. This result can be attributed to several factors; (a) low frequency of LOF alleles (b) absence of patients with the homozygous genotype for LOF alleles (c) high frequency CYP2C19 *1/*1 with CT suggestive of HPR (d) potential overestimation of patients HPR (technical limitation of PFA-200); (e) involvement of new intronic and/or promoter variants and (f) heterogeneity of response to clopidogrel due to genes not evaluated in this study [ 5 , 50 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, it has been established that the use of platelet function tests such as PFA-200, Verify Now P2Y 12 assay and others are potentially predictive of the clinical response to clopidogrel [ 20 , 49 ]. Although not significant, intermediate metabolizers (at least one loss function allele) showed a trend towards decreasing CT values and therefore are more susceptible to HPR.…”
Section: Discussionmentioning
confidence: 99%
“…PFA-200 testing involves an easily automated process that takes a short time to get the test results 11 , which is a high-shear system using whole blood rather than platelet-rich plasma 12 . It simulates the characteristics of physiological platelet function 13 and measures the closure time (CT) required for platelets to plug an aperture simulating an injured vessel 14 , after platelet activation by relevant stimuli, namely collagen and epinephrine (EPI), or collagen and adenosine diphosphate (ADP) 15 .…”
Section: Introductionmentioning
confidence: 99%
“…We conducted analyses to determine the impact of genetic variables on clopidogrel responsiveness, utilizing the CT value, that has been described as a potential predictive biomarker [ 24 26 ]. Bivariate analyses indicated that five SNPs were significantly associated.…”
Section: Discussionmentioning
confidence: 99%